Answer:
The first term of the sequence is a = 4
The sum of the first 13 terms is -480
Step-by-step explanation:
Given that:
The third term is: a + 2d = - 8 --- (1)
[tex]The \ sum \ of \ the \ first \ 10 \ terms \ is:[/tex]
[tex]-230 = \dfrac{10}{2}[2a+ (10-1)d][/tex]
[tex]-230 =5[2a+ (9)d][/tex]
-230 = 10a + 45d
10a + 45d = -230 ----(2)
From (1) and (2)
a + 2d = - 8
10a + 45d = -230
From (1), let a = -8 - 2d
Replace, the value of a in (1) to equation (2)
10(-8 -2d) + 45d = -230
-80 -20d +45d =-230
25d = -230 + 80
25d = -150
d = -150/25
d = -6
From equation (1);
a + 2(-6) = -8
a -12 = -8
a = -8 + 12
a = 4
Thus,the first term of the sequence a = 4
[tex]The \ sum \ of \ the \ first \ 13 \ terms \ is:[/tex]
[tex]S_n = \dfrac{n}{2}[2a+(n-1)d][/tex]
[tex]S_n = \dfrac{13}{2}[2(4)+(13-1)*-6][/tex]
[tex]S_n =7.5 [8+(12)\times -6][/tex]
[tex]S_n =7.5 [8-72][/tex]
= -480